Keberkesanan Program-program Pemulihan Tingkah Laku di Sekolah Henry Gurney dan Sekolah Tunas Bakti - Azizi Yahya, author 632921; Fakulti Pendidikan 8185 (Skudai : Penerbit Universiti Teknologi Malaysia, 2007)
The purpose of this study is to evalute the effectiveness of the programmes conducted by two rehabilitation centres for female delinquents. In these centres, the delinquents undergo programmes which aimed to give guidance and help the delinquents change their unwanted behaviour. The data were collected using questionnaires which was adapted from the research done by Azizi (1999) and Azizi (2004). Alpha Cronbach is used to test the reliability of this research. It showed that the overall Alpha value for the programmes is 0.93. A total of 79 respondents were chosen at simplified random to be the respondents of the research. The variables used in the research are the facilities, Vocational Programme, Co-curriculum Programme, Religious Programme and Counseling Programme. The overall findings of the research indicates that facilities and Counseling programme to be less effective compared to Vocational Programme, Co- curriculum Programme, Religious Programme. The results of the research showed that there is no significant difference in the way the facilities, Vocational Programme and Co-curriculum Programme was carried out in these two institution, namely Taman Seri Puteri Batu Gajah, Perak and Kompleks Dar-Assa’dah, Kuala Lumpur. There are significant differences between the Religious Programme and Counseling Programme in these two institutions.